Environmental problems in the coal mining industry in Russia. Issue 1 (October 2021) - Fatkulina, A V; Konokotin, D N; Koroleva, L A; Salov, S M; Samoylenko, D V
Abstract: The coal mining industry of Russia is characterized. Today, this industry is one of the most polluting types of human activity. The article provides a comprehensive assessment of the coal industry current impact on the environment, namely on the atmospheric air, the lithosphere, natural reservoirs, etc. The authors have analyzed the reasons and consequences of this industry negative impact on nature and man. The main sources of technogenic load on the environment during the coal deposits development are identified. Such sources include rock dumps, mine water, main ventilation fans, degassing installations, etc. The influence of rock dumps on the natural environment is investigated. The negative impact of the discharge of insufficiently treated mine water on the state of not only natural reservoirs, but also all components of the environment is shown. The composition of mine waters has been studied, which is important when choosing the technology for their treatment. Measures and methods to improve the environmental situation in the places of coal deposits development are considered. In particular, it is proposed to purify mine waters for the purpose of their use for technological, household, agricultural and other needs. The harmful and dangerous factors of the methane presence in the coal deposits development are shown. It is proposed to capture methane for further use, which will reduce its entry into the atmospheric air and at the same time make an economic profit. The principles of ensuring environmental safety in the coal mining industry are considered. Methods of reducing the anthropogenic load using the latest technologies are proposed. The conducted research is relevant and important for the further development of the coal mining industry in the framework of conservation and protection of the natural environment.